Equal pay legislation and the gender wage gap - Solomon W. Polachek (IZA World of Labor, 2014)
Despite equal pay legislation dating back 50 years, American women still earn 22% less than their male counterparts. In the UK, with its Equal Pay Act of 1970, and France, which legislated in 1972, the gap is 21% and 17% respectively, and in Australia it remains around 17%. Thus, the gender pay gap continues to be an important policy issue.
Keywords: J1; J12; J13; J16; J17; J7; J71; J78; 330; gender; wage inequality; human capital